UPAYA MENINGKATKAN KEMAMPUAN NILAI-NILAI MORAL DAN AGAMAMELALUI METODE SANDIWARABONEKA PADA ANAK USIA 5-6 TAHUNDI PAUD HUMAIRA PEKANBARU - Popong Nurhasanah; Zulkifli Zulkifli; Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this research is still to be found to encourage his protégé at the time the practice of praying, roughly speaking while playing, beat and seize when asked for a toy held by her friend, do not want to share and do not care about the people and told casually against the teacher. The aim of this study was to determine whether there is an increased ability of moral values and religion through puppet play and to know how much improvement occurs. This research is a classroom action research conducted in two cycles and each cycle is done 3 times the meeting. Each cycle consists of several stages, namely planning, implementation, observsi and reflection. Data collection tool used in this study in the form of sheets of observations taken from the results of the evaluation of each end of the cycle. This study involved one colleague or another teacher as an observer. The number of samples in this study were 12 children, consisted of 6 boys and 6 girls. Based on the results of data obtained an average percentage ability moral values and religion of the child before being given treatment equal to 38.3%. At Cycle I gained an average capability moral values and religion of the child, ie 50.7% whereas in Cycle II gained an average capability moral values and religion of the child, ie 77.1%. From the data obtained increased capacity of moral values and religious child first cycle was 32.3% and the second cycle by 52% so that the difference between Cycle I and Cycle II increase by 60% , It can be concluded that the method puppets can improve moral values and religion in children aged 5-6 years in early childhood Humaira Marpoyan Peace District of the city of Pekanbaru.Key word : puppet teathre, moral, religion2